Answer:
Explanation:
These are all the same types of questions so I will explain how you solve these and answer question #1 to get you started :)
for #1, y=3x+4
your first x value is -2.
You plug in the x value (which is -2 for the first box) into the equation (y=3x+4)
and you should get your first y value.
x=-2
y=3x+4
y=3(-2) + 4
y=-6+4
y= -2
therefore, #1 your first value of y is -2
The next x value is -1
Just plugin again!
y=3x+4
y=3(-1) + 4
y=-3+4
y= 1
Your second y value for #1 is -1
The third x value for #1 is 0
Same process: we plugin 0
y=3x+4
y=3(0) +4
y= 0+4
y=4
Your third y value for #1 is 4
Last x value for #1 is 2
Again, we plugin!
y=3x+4
y=3(2) +4
y= 6+4
y=10
Last y value for #1 is 10
I hope this helped! reach out if you need further explanation with questions 2-6!